VD_FINDINFO Arrêt / 2019 / 797 vom 30. September 2019 - VD Tribunal cantonal (2019)
DEMI-RENTE, RÉVISIONPRESTATION D'ASSURANCE, AGGRAVATION DE L'ATTEINTE À LA SANTÉ | 28 LAI, 4 LAI, 6 LPGA, 7 LPGA, 8 LPGA